Using behaviour change theory to train health workers on tobacco cessation support for tuberculosis patients: a mixed-methods study in Bangladesh, Nepal and Pakistan - Sahil Warsi; Helen Elsey; Melanie Boeckmann; Maryam Noor; Amina Khan; Deepa Barua; Shammi Nasreen; Samina Huque; Rumana Huque; Sudeepa Khanal; Prabin Shrestha; James Newell; et al. (BMC, 2019)
Abstract Background Low- and middle-income countries (LMICs) are disproportionately impacted by interacting epidemics of tuberculosis (TB) and tobacco consumption. Research indicates behavioural support delivered by health workers effectively promotes tobacco cessation. There is, however, a paucity of training to support LMIC health workers deliver effective tobacco cessation behavioural support. The TB and Tobacco Consortium undertook research in South Asia to understand factors affecting TB health workers' delivery of tobacco cessation behavioural support, and subsequently developed a training package for LMICs. Methods Using the "capability, opportunity, and motivation as determinants of behaviour" (COM-B) framework to understand any issues facing health worker delivery of behaviour support, we analysed 25 semi-structured interviews and one focus group discussion with TB health workers, facility in-charges, and national tuberculosis control programme (NTP) staff members in each country. Results were integrated with findings of an adapted COM-B questionnaire on health worker confidence in tobacco cessation support delivery, administered to 36 TB health workers. Based on findings, we designed a guide and training programme on tobacco cessation support for health workers. Results Qualitative results highlighted gaps in the majority of health workers' knowledge on tobacco cessation and TB and tobacco interaction, inadequate training on patient communication, insufficient resources and staff support, and NTPs' non-prioritization of tobacco cessation in all three countries. Questionnaire results reiterated the knowledge deficits and low confidence in patient communication. Participants suggested strengthening knowledge, skills, and competence through training and professional incentives. Based on findings, we developed an interactive two-day training and TB health worker guide adaptable for LMICs, focusing on evidence of best practice on TB and tobacco cessation support, communication, and rapport building with patients. Conclusions TB health workers are essential in addressing the dual burden of TB and tobacco faced by many LMICs. Factors affecting their delivery of tobacco cessation support can be identified using the COM-B framework, and include issues such as individuals' knowledge and skills, as well as structural barriers like professional support through monitoring and supervision. While structural changes are needed to tackle the latter, we have developed an adaptable and engaging health worker training package to address the former that can be delivered in routine TB care. Trial registration ISRCTN43811467.